In vitro antibacterial and antibiotic modifying activity of crude extract, fractions and 3',4',7-trihydroxyflavone from Myristica fragrans Houtt against MDR Gram-negative enteric bacteria - Joachim K. Dzotam; Ingrid Konga Simo; Gabin Bitchagno; Ilhami Celik; Louis P. Sandjo; Pierre Tane; Victor Kuete (BMC, 2018)
Abstract Background Nutmeg is the seed kernel inside the fruit of Myristica fragrans Houtt. (Myristicaceae). It possesses various pharmacological activities but is used in Cameroon only for its flavor in making cakes. The present study thus aimed to investigate the in vitro antibacterial activity and antibiotic modifying activities of crude seed kernel methanol extract (MFS), fractions (MFSa-e) as well as 3',4',7-trihydroxyflavone from Myristica fragrans against a panel of multi-drug resistant (MDR) Gram-negative bacteria. Methods The modified rapid p-iodonitrotetrazolium chloride (INT) colorimetric assay was used to determine the Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) on the tested bacteria, as well as those of antibiotics in association with the extract and/or isolated compound. Column chromatography was used for the fractionation and purification of the seed kernel extract whilst the chemical structures of compounds were determined using spectroscopic techniques. Results Phytochemical investigations lead to the isolation of 3',4',7-trihydroxyflavone from the fraction MFSb. The crude extract showed antibacterial activity with MICs ranging from 32 to 1024 μg/mL on the majority of the 29 tested Gram-negative bacterial strains. Fraction MFSb inhibited the growth of 100% (29/29) of the tested bacterial strains, as well as the compound 3',4',7-trihydroxyflavone (12/12) with a MIC values ranging from 32 to 1024 μg/mL, and 4 to 128 μg/mL respectively. The lowest MIC value (4 μg/mL) was recorded with 3',4',7-trihydroxyflavone against Providencia stuartii ATCC299645 as well as the best MBC value (16 μg/mL) against the same strain. In the presence of Phenylalanine-Arginine-β-Naphthylamide (PAßN), an efflux pumps inhibitor, the activity of the extract increased on 73.33% (11/15) meanwhile that of 3',4',7-trihydroxyflavone increased on 100% tested bacteria. The compound 3',4',7-trihydroxyflavone potentiated the activity of antibiotics in the majority of the tested bacterial strains. Conclusion The results of the present work provide additional information on the use of nutmeg and it major antibacterial component, 3',4',7-trihydroxyflavone, as a potential drug in the treatment of bacterial infections including multidrug resistant phenotypes.